Essential Oil Composition of Grimmia trichophylla Grew and G. decipiens (Shultz) Lindb. Grown in Turkey - Beyza Cansu, Tayyibe; Ucuncu, Osman; Kahriman, Nuran; Ozdemir, Turan; Yayl, Nurettin (Asian Journal of Chemistry, 2010)
The essential oils obtained by hydrodistillation from Grimmia trichophylla Grew and G. decipiens (Shultz) Lindb. were analyzed by GC-FID and GC-MS. Twenty-three compounds in the oil of G. trichophylla, representing 76.7 % and 32 compounds in the oil of G. decipiens, representing 65.6 %, were identified. The essential oils are rich in aldehydes (24.3 and 17.4 %) and hydrocarbons (18.3 and 23.5 %) with 2E-nonenal (9.8 %), nonanal (6.3 %), tricosane (5.1 %) and cyclotetradecane (3.7 %) as the major components, respectively.